Interaksi Antara Strategi Pembelajaran Resource-Based-Learning (RBL) dan Think-Pair-Share serta Minat Belajar SiswaTerhadap Aktivitas Belajar Siswa Pada Mata Pelajaran IPA di Kelas VII SMP Untuk Materi Upaya Mengatasi Kerusakan dan Pencemaran Lingkungan - Zohra Hiola (LP2M IAIN Sultan Amai Gorontalo, 2017)
The aims of this aticle is to know interaction between gift of different learning strategy (Resource-Based-Learning and Think-Pair-Share) and student learning interest and learning activity of student at effort matter overcomes damage and contamination of environment. This article explained about the result of study at class VII in SMP Negeri 10 Kota Gorontalo, with experiment method and applies data analysis ANAVA The result showing there are interaction between learning strategies and student learning interest with student learning activity, for student having high learning interest, usage of learning strategy RBL is higher than learning strategies TPS, for student having low learning interest, usage of learning strategy RBL and TPS doesn't gived acquirement difference of the student learning activity.